Reviewing regulations and stakeholder perceptions of ride-sharing technical requirements in Indonesia - Suartika, I Made; Maryudi, Ahmad; Djunaedi, Achmad; Darwin, Muhadjir M. (Interdisciplinary Social Studies, 2024)
In Indonesia, the Application-Based Taxis (ABT) operators argue that they are not required to undergo periodic testing, unlike in other countries. This research aims to address this issue by conducting a qualitative study using three approaches: regulatory review, comparison of policies from other countries, and in-depth interviews with ABT company officials and 100 drivers. The study found that 41% of drivers refused to follow the regulation, citing financial burdens. The study proposes that ABT vehicles undergo periodical testing for four years, repeated annually, similar to other countries. Random inspections of ABT vehicles on the road are also recommended to increase awareness of vehicle maintenance, with a focus on tire and brake condition. This study aims to improve the roadworthiness of ABT vehicles in Indonesia.